RAGE-dependent activation of gene expression of superoxide dismutase and vanins by AGE-rich extracts in mice cardiac tissue and murine cardiac fibroblasts - Leuner, Beatrice; Bierhaus, Angelika (Food & function, 2012)
Advanced glycation end products (AGEs) are stable compounds formed from initial Maillard reaction products. They are considered as markers for ageing and often associated with age-related, degenerative diseases. Bread crust represents an established model for nutritional compounds rich in AGEs and is able to induce antioxidative defense genes such as superoxide dismutases and vanins in cardiac cells. The aim of this study was to investigate to what extend the receptor for AGEs (RAGE) contributes to this response. Signal transduction in response to bread crust extract was analysed in cardiac fibroblasts derived from C57/B6-NCrl (RAGE +/+) and the corresponding RAGE-knock out C57/B6-NCrl mouse strain (RAGE −/−). Activation of superoxide dismutases in animals was then analysed upon bread crust feeding in these two mice strains. Cardiac fibroblasts from RAGE −/− mice did not express RAGE, but the expression of AGER-1 and AGER-3 was up-regulated, whereas the expression of SR-B1 was down-regulated. RAGE −/− cells were less sensitive to BCE in terms of MAP-kinase phosphorylation and NF-κB reporter gene activation. Bread crust extract induced mRNA levels of MnSOD and Vnn-1 were also reduced in RAGE −/− cells, whereas Vnn-3 mRNA accumulation seemed to be RAGE receptor independent. In bread crust feeding experiments, RAGE −/− mice did not exhibit an activation of MnSOD-mRNA and -protein accumulation as observed for the RAGE +/+ animals. In conclusion, RAGE was clearly a major factor for the induction of antioxidant defense signals derived from bread crust in cardiac fibroblast and mice. Nevertheless higher doses of bread crust extract could overcome the RAGE dependency in cell cultures, indicating that additional mechanisms are involved in BCE-mediated activation of SOD and vanin expression.